FINANCIAL STABILITY AND INVESTMENT ATTRACTIVENESS OF THE HOTEL BUSINESS ENTERPRISES: THEORETICAL ASPECTS AND PRACTICAL ANALYSIS - Baranova, Natalia; Bogatyreva, Liudmila (PEOPLE: International Journal of Social Sciences, 2017)
The article discusses some methodological issues of evaluating financial stability and investment attractiveness of the hotel enterprises. The essence and the contents of the tasks dealing with the analysis of these categories, the known methods, the procedure of calculation of the indicators and their meaning are considered. The aim of this work is to analyze financial stability and investment attractiveness of the hotel business enterprises and to consider the theoretical aspects of this problem. For achieving this goal, methods of comparison and statistical methods were applied. The thesis has been formulated that for attracting financial resources an enterprise (organization) should have relatively stable values of a number of indicators, which confirm the sustainability of their development. The figures were calculated in dynamics from 2011 to 2015 basing on the hotel business reports data, with the help of the methodology of assessing financial stability and investment attractiveness of the company INEC.